Management of Pericoronitis of Newly-erupted Permanent Tooth using Electrosurgery–A Case Report - Stephani Dwiyanti Indrasari (Cermin Dunia Kedokteran, 2016)
Pericoronitis is an inflammation of gingival tissue surrounding the coronal portion of a tooth. Treatment for pericoronitis is aimed at management of the acute phase, followed by resolution of the chronic condition. Six-year-old boy came with a dull pain on his lower left gum, diagnosed as pericoronitis on gingival region 36, caused by plaque, worsened by secondary trauma during mastication as well as food retention in inflamed gingiva. The treatment plan for the pericoronitis on this patient was operculectomy using electrosurgery.